Biogeochemical cycles for combining chemical knowledge and ESD issues in Greek secondary schools part I: designing the didactic materials. Issue 1 (29th October 2015) - Koutalidi, Sophia; Scoullos, Michael
Abstract : Biogeochemical cycles support all anthropogenic activities and are affected by them, therefore they are intricately interlinked with global environmental and socioeconomic issues. Elements of these cycles that are already included in the science/chemical curriculum and textbooks intended for formal education in Greek secondary schools were thoroughly reviewed and on the basis of the gaps and needs identified new didactic materials were produced. The didactic materials were designed in order to enhance the comprehension of the biogeochemical cycles (of water, carbon, nitrogen, phosphorus and sulphur) and include educational content and guidance to achieve ESD goals including strengthening of students' environmentally-friendly attitudes and commitment towards sustainability. These materials clarify the function of the cycles supplementing chemical knowledge and scientific information relevant to the real world phenomena and conditions ( e.g. climate change, ocean acidification, eutrophication) that learners could experience, connecting them with sustainable development issues (sustainable consumption and production, renewable energies, etc. ). The materials were assessed as successful by educators and students through experimental implementation in 16 Greek secondary schools. The present article (Part I of the research) focuses on the aim, content and design of the didactic materials while in Part II, assessment of their impact on the knowledge and attitudes of students is presented.